2003
DOI: 10.1046/j.1469-8137.2003.00744.x
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal cycles in the germination capacity of buried seeds of some Leguminosae (Fabaceae)

Abstract: Summary• The influence of seasonal factors on the germination of impermeable seeds of Fabaceae was studied. Seeds of 14 herbaceous species were buried for up to 2.5 yr and exposed to natural seasons. At regular intervals, seeds were exhumed and germination was tested in four different temperature regimes. Some species had a very low percentage germination regardless of season, others germinated predominantly in the autumn.• Six species showed a marked seasonal cycle with high germination percentages in spring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
159
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 161 publications
(168 citation statements)
references
References 24 publications
(29 reference statements)
5
159
1
1
Order By: Relevance
“…In European heath in the Mediterranean, daily temperature cycles occurring in vegetation gaps promoted germination in the gorse Ulex parviflorus (Baeza and Roy 2008). In temperate European ecosystems, Van Assche et al (2003) found that slight seasonal changes in daily temperature fluctuations were key to breaking physical dormancy of many herbaceous legumes. Other evidences have been highlighted from studies on invasive species, such as the gap recruitment displayed by the tropical shrub Mimosa pigra (Lonsdale 1993) and the European gorse, U. europaeus in New Zealand (Ivens 1983).…”
Section: Discussionmentioning
confidence: 99%
“…In European heath in the Mediterranean, daily temperature cycles occurring in vegetation gaps promoted germination in the gorse Ulex parviflorus (Baeza and Roy 2008). In temperate European ecosystems, Van Assche et al (2003) found that slight seasonal changes in daily temperature fluctuations were key to breaking physical dormancy of many herbaceous legumes. Other evidences have been highlighted from studies on invasive species, such as the gap recruitment displayed by the tropical shrub Mimosa pigra (Lonsdale 1993) and the European gorse, U. europaeus in New Zealand (Ivens 1983).…”
Section: Discussionmentioning
confidence: 99%
“…Legume seeds are known to have physical dormancy (Baskin, 2003;Van Assche et al, 2003;Venier et al, 2012;Gehan-Jayasuriya et al, 2013), as Mimosa species (Martínez-Pérez et al, 2006;Gehan-Jayasuriya et al, 2013). Prior to any assay, all Mimosa seeds were washed with commercial detergent (3 g/100 ml water/3 min) (Camargo-Ricalde and Grether, 1998).…”
Section: Experimental Designmentioning
confidence: 99%
“…Under natural conditions, it has been suggested that exposition of seeds to high or fluctuating temperatures is the responsible for seed dormancy alleviation (Vazquez-Yanes & Orozco-Segovia, 1982;Van Assche et al, 2003), whereas in laboratory conditions, the mechanical, thermal and chemical scarification, would be the most effective dormancy-breaking treatments (Baskin & Baskin, 2014). In this case, wet heat (≥ 80 °C), acid and mechanical scarification were effective methods to break seed dormancy, depending on the species.…”
Section: Discussionmentioning
confidence: 99%